Inflammation and joint destruction may be linked to the generation of cartilage metabolites of ADAMTS-5 through activation of toll-like receptors. Issue 5 (May 2020) - Sharma, N.; Drobinski, P.; Kayed, A.; Chen, Z.; Kjelgaard-Petersen, C.F.; Gantzel, T.; Karsdal, M.A.; Michaelis, M.; Ladel, C.; Bay-Jensen, A.C.; Lindemann, S.; Thudium, C.S.
Summary: Objective: Links between pain and joint degradation are poorly understood. We investigated the role of activation of Toll-like receptors (TLR) by cartilage metabolites in initiating and maintaining the inflammatory loop in OA causing joint destruction. Methods: Synovial membrane explants (SMEs) were prepared from OA patients' synovial biopsies. SMEs were cultured for 10 days under following conditions: culture medium alone, OSM + TNFα, TLR2 agonist - Pam2CSK4, Pam3CSK4 or synthetic aggrecan 32-mer, TLR4 agonist - Lipid A. Release of pro-inflammatory and degradation biomarkers (acMMP3 and C3M) were measured by ELISA in conditioned media along with IL-6. Additionally, human cartilage was digested with ADAMTS-5, with or without the ADAMTS-5 inhibiting nanobody - M6495. Digested cartilage solution (DCS) and synthetic 32-mer were tested for TLR activation in SEAP based TLR reporter assay. Results: Western blotting confirmed TLR2 and TLR4 in untreated OA synovial biopsies. TLR agonists showed an increase in release of biomarkers - acMMP3 and C3M in SME. Synthetic 32-mer showed no activation in the TLR reporter assay. ADAMTS-5 degraded cartilage fragments activated TLR2 in vitro. Adding M6495 – an anti-ADAMTS-5 inhibiting nanobody®, blocked ADAMTS-5-mediated DCS TLR2 activation. Conclusion: TLR2 is expressed in synovium of OA patients and their activation by synthetic ligands causes increased tissue turnover. ADAMTS-5-mediated cartilage degradation leads to release of aggrecan fragments which activates the TLR2 receptor in vitro . M6495 suppressed cartilage degradation by ADAMTS-5, limiting the activation of TLR2. In conclusion, pain and joint destruction may be linked to generation of ADAMTS-5 cartilage metabolites.